2019
DOI: 10.1089/end.2019.0400
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in the Frequency of Presentation with Acute Ureteral Colic and Its Association with Meteorologic Factors

Abstract: Introduction: A seasonal variation in the frequency of acute stone presentations has been observed in studies from the United States, Africa, and Asia. The increased incidence of acute stone presentations during periods of warm weather has been attributed to both the dehydrating effect of elevated temperatures and the vitamin D related increase in calciuria during periods of increased sunshine. The aim of this study is to establish whether the association between various meteorologic parameters and the frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Regarding other NCDs, in our Irish search of the literature, Roche et al [44] found an association during the summer months in Ireland (Dublin), for an increased frequency of presentations to Emergency Departments for acute renal stones. Furthermore, a study conducted by Flaherty et al [55] suggested that specific travel advice should be provided to obese people that may exhibit poor heat tolerance travelling to warm climates.…”
Section: Chronic Conditionsmentioning
confidence: 82%
See 2 more Smart Citations
“…Regarding other NCDs, in our Irish search of the literature, Roche et al [44] found an association during the summer months in Ireland (Dublin), for an increased frequency of presentations to Emergency Departments for acute renal stones. Furthermore, a study conducted by Flaherty et al [55] suggested that specific travel advice should be provided to obese people that may exhibit poor heat tolerance travelling to warm climates.…”
Section: Chronic Conditionsmentioning
confidence: 82%
“…In the global meta-analysis conducted by Bouchama et al [42] [43]. Roche et al [44] in their analysis of computer tomography kidney, ureters and bladder scans in an Irish hospital group, did find that older adults (> 65 years) were more susceptible to ureteral colic during warm weather compared to those below 65 years old, potentially due to an increased susceptibility to dehydration. Older adults (> 75 years) were identified as a particularly vulnerable group in Pascal et al's [26] study of heatwaves and mortality in Ireland.…”
Section: Older Peoplementioning
confidence: 99%
See 1 more Smart Citation